Visual acuity and microperimetric mapping of lesion area in eyes with inflammatory cystoid macular oedema. (27th June 2013) - Munk, Marion R.; Kiss, Christopher G.; Huf, Wolfgang; Montuoro, Alessio; Sulzbacher, Florian; Kroh, Maria; Larsen, Michael; Schmidt‐Erfurth, Ursula
Abstract. Purpose: To evaluate the effect of fluid accumulation on local visual function in inflammatory cystoid‐macular‐edema (ICME). Methods: This cross‐sectional study applied optical‐coherence‐tomography over a 12 × 12 fovea‐centered field in 50 patients with ICME and mapped the extent of fluid‐filled spaces in various retinal layers, of subretinal‐fluid and of diffuse‐edema. Regression analysis examined effect of planimetric fluid‐distribution on best‐corrected‐visual‐acuity (BCVA) and mean microperimetric‐sensitivity. Results: BCVA decreased with increasing central‐neuroretinal‐thickness (r = 0.52, p = 0.001), total central‐retinal‐thickness, including subneuroretinal‐fluid (r = 0.41, p = 0.006), total cystoid‐and‐diffuse edema‐area (r = 0.35, p = 0.036) and cystoid inner‐nuclear‐layer area (r = 0.39, p = 0.02). Mean retinal‐sensitivity decreased with increasing diffuse edema‐area (r = −0.86, p < 0.0001), total cystoid‐and‐diffuse edema‐area (r = −0.54, p = 0.001), cystoid inner‐nuclear‐layer area (r = −0.46, p = 0.008) and cystoid ganglion‐cell‐layer area (r = −0.6, p = 0.049), central‐neuroretinal‐thickness (r = −0.42, p = 0.028) and total central‐retinal‐thickness (r = −0.34, p = 0.039). In multivariate‐analyses BCVA was best described by central‐neuroretinal‐thickness, duration of edema, total cystoid‐and‐diffuse edema‐area and cystoid inner‐nuclear‐layer area (R2 = 0.5, p = 0.002). Mean retinal‐sensitivity was best described by diffuse edema‐area, total cystoid‐and‐diffuse edema‐area and central‐neuroretinal‐thickness (R2 = 0.75, p < 0.0001). Subretinal‐fluid area and cystoid outer‐nuclear/Henle's layer area had no effect on either BCVA or microperimetry. Conclusions: Thickening of the neurosensory‐fovea, not subfoveal‐fluid, had major impact on both BCVA and retinal‐sensitivity. The extent of edema in inner retinal layers also had major impact on both of these two functional parameters. Visual‐impairment seems to differ depending on the layers involved, thus different types of fluid accumulation may potentially be given varying treatment priorities.